Revised Measure of Environmental Qualities of Activity Settings (MEQAS) for youth leisure and life skills activity settings. Issue 15 (16th July 2016) - King, Gillian; Rigby, Patty; Avery, Lisa
Abstract: Purpose : The aim was to create an expanded version of a published observer-rated Measure of Environmental Qualities of Activity Settings (MEQAS-32). Method : Testing was conducted using a diverse sample of activity settings. Raters completed the original MEQAS questionnaire (MEQAS-66) for 76 youth leisure and life skills activity settings. Scales for the revised measure (MEQAS-48) were determined using a two-step approach: (a) developing a theoretically-based model based on item-to-item linkages, and (b) confirmatory factor analysis. Results : The analysis revealed a good fitting 9-factor model (CFI= 0.965, RMSEA= 0.049). Five of the six MEQAS-32 scales remained and were validated in an independent dataset. Four additional scales were identified in the MEQAS-48: Comfortable Place-related Qualities, Opportunities for Privacy/Relaxation, Opportunities to Interact with Peers, and Opportunities for Cooperative Group Activity. Opportunities for Choice and Opportunities for Personal Growth were significantly correlated with corresponding youth experiences. Construct validity was demonstrated through predictions for various types of activities. Conclusion s: The MEQAS-48 more completely reflects the original conceptualization of the measure's content than does the MEQAS-32. Findings suggest the increased utility of the measure due to broader coverage of environmental qualities. The MEQAS-48 can be used to assess environmental qualities for research, program design, and clinical practice. Implications for Rehabilitation: The MEQAS is the first observer-completed measure of environmental qualities of activity settings. Compared to the MEQAS-32, the MEQAS-48 captures a broader range of important environmental qualities, including comfortable place-related qualities, and opportunities for privacy/relaxation, peer interaction, and cooperative group activity. The MEQAS-48 has clinical utility for use in program design and development, and research utility for understanding environmental qualities.